Graphene modified electrospun poly(vinyl alcohol) nanofibrous membranes for glucose oxidase immobilization - C. M. Wu; S. A. Yu; S. L. Lin (eXPRESS Polymer Letters, 2014)
In this study, poly(vinyl alcohol) (PVA)/Glucose oxidase (GOx)/graphene biocomposite membranes were prepared using an electrospinning technique and used for enzyme immobilization. The PVA/GOx/graphene membrane’s morphology was examined by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), while its electrochemical sensitivity was studied by chronoamperometry. Kinetic parameters were determined to clarify the role of graphene in enzyme immobilization, while a spectrophotometric assay was used to quantify the active enzyme. The results indicated that the presence of graphene helps to stabilize the enzyme’s conformation, facilitate the catalytic reaction, and increase the survivability of the enzyme.